Aplikasi Pendaftaran dan Penyerahan Berkas Persyaratan Nikah KUA Kec. Koto Tangah Padang - Turaina, Rifa (Universitas Putera Batam, 2021)
The Office of Religious Affairs or abbreviated as KUA has the functions of implementing marriage registration, referring, managing and fostering mosques, zakat, endowments, other social services and developing sakinah families, but what is very common in the KUA community is only a place to register and hold marriages. In KUA, the Koto subdistrict for the process of registering the bride and groom (catin) is still done by recording the ledger so that there is no guarantee the data will be stored and neatly organized. Then this research purpose of registering and submitting catin files which will be conducted online. So that the process of registering and submitting catin files will be stored in the database and safeguarding the data will be safer. Data collection techniques from this study were directly involved in the field with direct observation of the catin registration process, direct interviews and literature studies by using the System Development Life Cycle method. With this application, it is expected to be able to assist KUA officers and catin in the registration process so that the best service in the KUA office of Koto Tangah sub-district is created. Keyword : Applications, marriage, online